Analisis Kesantunan Tuturan Imperatif Dalam ProsesPembelajaran Bahasa Indonesia Di Kelas VII SMPNegeri 1 Kartasura Tahun Pelajaran 2015/2016 - Agustiana Puspitasari, Risty (2016)
This study has two objectives to 1) describe the type of speech imperative that used in Indonesian learning interaction in class VII SMP Negeri 1 Kartasura in the school year 2015/2016, and 2) to describe the speech politeness imperative contained in Indonesian learning interaction in class VII SMP State 1 Kartasura academic year 2015/2016. This research is descriptive qualitative. The subject of this research that Indonesian teachers and students of class VII in SMP Negeri 1 Kartasura academic year 2015/2016. Object of research is imperative utterances that occur during the process of learning Indonesian in class VII SMP Negeri 1 Kartasura academic year 2015/2016. The data in this study is a narrative imperative form of the word, or phrase in the communication between teachers and students containing speech imperatives for the learning process in the classroom. The data sources Indonesian learning interaction in class VII SMP Negeri 1 Kartasura academic year 2015/2016. Data collection techniques used in the study are recording technique and technique refer to note. This study uses two kinds of triangulation, the first triangulation techniques or methods of collecting data and the second data method. The data analysis technique used in this research that a unified method.Results of this study can be concluded that: 1) The types of speech Imperative Used in Indonesian Language Learning Interactions in Class VII SMP Negeri 1 Kartasura academic year 2015/2016, covering Imperative Sentence Request, Sentences Imperative to grant licenses, solicitation Imperative Sentence, Sentence Imperative Commands, 2) Politeness speech imperatives contained in Indonesian Language Learning Interactions in Class VII SMP Negeri 1 Kartasura academic year 2015/2016, covering: declarative construction, construction imperative, interrogative construction,and construction eksklamatif.